Emergence of third-generation cephalosporins and carbapenems resistant uropathogenic gram-negative bacteria in Malawi: a threat to public health - Dr Gabriel Kambale Bunduki; Dr Peter Nambala; Mr Alfred Limani; Mr Chisomo Nkhoma; Professor Nicholas Feasey; Professor Janelisa Musaya (International Journal of Infectious Diseases)
Background: Urinary tract infections (UTIs) are common healthcare-associated infections (HCAIs) and the leading cause of morbidity among surgical patients. Strains that produce extended-spectrum beta-lactamases or carbapenemases are both particularly problematic and disproportionately impact resource-limited healthcare settings where last-line antimicrobials may not be available. This study aimed to determine the resistance rates to third-generation cephalosporins and carbapenems among uropathogenic gram-negative bacteria from surgical patients colonised and with UTI in Malawi. Methods: A hospital-based, prospective cross-sectional study was conducted in the surgical department of Queen Elisabeth Central Hospital in Blantyre, Malawi, from August to October 2020. Consecutive surgical patients were recruited, and urine samples screened by dipstick irrespective of UTI symptoms and cultured. Significant bacteriuria was defined as a pure culture with ≥10⁵ CFU/mL. Antimicrobial susceptibility testing was determined using the disc diffusion method and interpreted using the EUCAST guidelines. Data were analysed using SPSS 28 software. Results: A total of 1125 patients were screened for UTI, and 337 patients had urine samples processed for culture following a positive dipstick. Significant growth was observed in 53.1% (179/337). The prevalence of symptomatic UTI was 2.3% (26/1125) and were all catheter-associated UTI (28.9%, 26/90). Gram-negative bacteria were the most prevalent isolates (155/179) with the predominance of E. coli (53.5%, 83/155), Citrobacter spp. (11%, 17/155), Enterobacter spp. (6.5%, 10/155), Acinetobacter spp. (5.8%, 9/155), and Pseudomonas spp. (3.9%, 6/155). Overall, 74.3% (104/140) Enterobaterales were third-generation cephalosporin resistant and 1.4% (2/140) were meropenem. 22.2% (2/9) of Acinetobacter spp. were meropenem resistant while none of the Pseudomonas spp. was resistant to meropenem. However, 66.7% (4/6) of Pseudomonas spp. were third-generation cephalosporin resistant. Discussion: Multidrug-resistant patterns due to third-generation cephalosporin and carbapenem-resistant gram-negative bacteria are now becoming prevalent in hospitals worldwide, posing a public health challenge. These bacteria require global monitoring to maintain awareness of prevalent and emerging resistance mechanisms and to inform treatment and infection prevention strategies. Conclusion: Third-generation cephalosporin and carbapenem-resistant bacteria are rapidly proliferating in Malawi. This highlights the need for improved infection prevention and control practices and enhanced surveillance to limit the dissemination of these bacteria.